ANALISIS FIQH ZAKAT HARTA KONTEMPORER DENGAN METODE QIYAS - Iman Santoso; Didin Hafidhuddin; Hendri Tanjung (Kasaba, 2019)
Zakat is the third pillar of Islam after syahadat and prayers, since zakat is a pillar of the faith which is very important and strategic. The reseach analysis that conducted in this discussion on fiqh of zakat of treasure is qiyas or analogical method. In conclusion, in order to answer the problem of contemporary zakat Muslim scholars must master three things: first, understanding and mastering the ushul fiqh especially that related to qiyas; second, mastering the requirements of treasure that has to be given as zakat; third, understanding the five models on standard zakat of treasure